Poverty and Social Exclusion in Romania: A Consensual Approach to Material Deprivation - Stănescu, Iulian; Dumitru, Mihai (Calitatea Vieții, 2017)
This paper explores through a consensual approach the extent and dimensions of material deprivation in Romanian society in the early 2010s. First, we provide an overview of poverty and inequality issues in Romania since 1990, focused on the structural causes and the profile of the population facing the risk of poverty. The second part of the paper deals with material deprivation and the use of the consensual method in its measuring. We begin with the AROPE indicator and the British Social Exclusion Matrix, which feature the consensual approach in measuring material deprivation. From this, we briefly look at different methodological approaches in academic research on the issues of poverty and social exclusion in Romania. The survey data is then used in a consensual approach towards measuring material deprivation in Romania.